PENGARUH METODE DISCOVERY TERHADAP SISWA DALAM MEMAHAMI MATERI BAHASA ARAB KELAS XI IIA 2 MADRASAH ALIYAH UNGGULAN KH.A.WAHAB HASBULLOH TAMBAKBERAS JOMBANG - Dini Sirma Budi; Chusnul Chotimah; Rina Dian Rahmawati (Al-Lahjah, 2019)
This study discusses "The use of the Discovery Method to understanding Arabic material in the Superior Aliyah Madrasah KH.A.Wahab Hasbulloh Tambakberas Jombang". The purpose of using this Discovery Method for understanding Arabic material in Madrasas is to know the level of mastery of Arabic material, its advantages and disadvantages in learning activities in Madrasah Aliyah Featured KH. A. Wahab Hasbulloh Tambakberas Jombang. The step taken by the teacher is the teacher gives the learning material immaturely (indirectly so) then students process it. Research with quantitative methods uses the type of experimental research (trials) with ordinal data types. While the data collection method uses the discation method . As for the results of these data it has been proven that there is an influence of the Discovery Method on the mastery of material in KH Aliadah Wahhab, KH.A.Wahab Hasbulloh By using this method, students are more active and more effective in learning Arabic subjects. Keywords: Discovery Method, understanding of material.